1999
DOI: 10.2307/1244454
|View full text |Cite
|
Sign up to set email alerts
|

Farm Growth and Survival: Econometric Evidence for Individual Farms in Upper Austria

Abstract: This article investigates survival and growth of more than 50,000 Upper Austrian farm households within a maximum likelihood sample selection framework. The results suggest that age, schooling and sex of the farm operator, size of the farm family, and off-farm employment status, as well as initial farm size, significantly influence farm growth and survival. The present study provides support for the notion of a “disappearing middle” in the size distribution. The process of polarization is closely related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
153
3
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(188 citation statements)
references
References 25 publications
16
153
3
7
Order By: Relevance
“…As determined by Weiss (1999b), Kimhi and Bollman (1999), and Juvančič (2002Juvančič ( , 2006, the probability of farm exit even decreases as the owner's age approaches 43, 44, or 45, but it continually increases after this. Weiss (1999b) connects this with the 'life cycle effect. ' These findings confirm the correctness of the decision to include only owners 45 and older in the sample.…”
Section: Study Sample and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As determined by Weiss (1999b), Kimhi and Bollman (1999), and Juvančič (2002Juvančič ( , 2006, the probability of farm exit even decreases as the owner's age approaches 43, 44, or 45, but it continually increases after this. Weiss (1999b) connects this with the 'life cycle effect. ' These findings confirm the correctness of the decision to include only owners 45 and older in the sample.…”
Section: Study Sample and Methodsmentioning
confidence: 99%
“…The first study (Weiss 1999a) examined human capital, the off-farm employment, the characteristics of the owner and farm family, and other characteristics of the farm and how they affect its survival. The second study (Weiss 1999b) examined the characteristics of the owner and his/her family, the farm, and the offfarm employment of the owner and his partner and how these affect farm exit. A study of farms in Upper Austria by Stiglbauer and Weiss (2000) describes how the characteristics of the farm family and farm affect the actual succession on the farm and farm exit.…”
Section: Factors In Studies From the Eu Countriesmentioning
confidence: 99%
“…agriculture [4,5]. Conversely, other studies support that off-farm employment fosters the structural change in agriculture [6].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have showed that off-farm employment is complementary to farm work and slows down the exit from agriculture [4,5]. Conversely, other studies support that off-farm employment fosters the structural change in agriculture [6]. agriculture [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Otros son de carácter más general como el nivel de renta, la tasa de desempleo, las tendencias demográficas, la capacidad industrial, las economías de aglomeración, el tipo de interés y la inversión pública en investigación y desarrollo (Zepeda, 1995;Weiss, 1999;Breustedt y Glauben, 2007;Latruffe et al, 2013).…”
Section: Ajuste Agrariounclassified